Mean platelet volume count as a risk factor for bloodstream infection in Pediatric Ward Sanglah General Hospital Denpasar, Bali-Indonesia - Ni Putu Wirantari; I Wayan Gustawan; Made Gede Dwilingga Utama; Bagus Ngurah Putu Arhana; Ni Nengah Dwi Fatmawati; Ni Made Adi Tarini (DiscoverSys Inc., 2020)
Background: Mean platelet volume (MPV) is a potentially interesting parameter in predicting bacteremia in patients admitted with suspected community-acquiredÂ infections. The incidence of bacteremia, defined as the presence of viable bacteria in the bloodstream, in patients who were being admitted to hospital. Multiple recent studies have confirmed that low-level bacteremia is more common than previously thought, occurring in 38% to 68% of all pediatric patients with a positive blood culture. The mortality rate is 25%â€“30%, increases to 50% when associated with severe sepsis. The objective of this study is to investigate whether MPV as a risk factor for bloodstream infection.Methods: This was a hospital-based case-control study, review of the medical record from January 2016 until December 2018. We collect age, gender, MPV, platelet and blood culture. We analyze the association between MPV to bloodstream infection.Result: Between January 1st 2016 and December 31st 2018, there were 86 patients with positive blood cultures and 89 negative blood cultures. In the case group, there were 48 (53.9%) male and 41 (46.1%) female subjects, while in the control group there were 63 (73.3%) male and 23 (26.1%) female subjects. The median age for case group was 14 months while the median age for control group was 23 months. From the ROC curve, the optimal cutoff value for MPV was determined as 5.59. The odd ratio determined the relationship between MPV to blood stream infection was 2,26 with 95% CI 1.13-4.52. The adjusted odds ratio was 2.24 95% CI (1.10-4.57). The majority diagnosis was pneumonia (46.1%) in case group then early onset neonatal sepsis (28.1%) and meningitis (7.9%).Conclusion: The MPV â‰¥5.59 is a risk factor for developed bloodstream infection. This result can be used as a cutoff point to initially administered antibiotic to prevent the worse prognosis (sepsis, multiple organ failure, and death).